ARHGAP4 Inhibits Proliferation and Growth of SW620 Colon Cancer Cells by Cell Cycle and Differentiation Pathways - Ming-Sheng Fu; Shu-Xian Pan; Xun-Quan Cai; Cui-Ting Lv; Qin-Cong Pan (Scientifica)
The aim of this study is to explore the mechanism by which ARHGAP4 regulates the proliferation and growth of colon cancer cells, and it relates to the metastasis of colorectal cancer (CRC). Various techniques including western blot, CCK8, qRT-PCR, RNA seq assay, plate cloning, subcutaneous tumorigenesis assays, and bioinformatics tools were employed to identify genes that were upregulated or downregulated upon ARHGAP4 knockdown and their involvement in tumor cell proliferation and growth. The expression of ARHGAP4 in T and M stages of CRC uses immunohistochemistry. The expression levels of ARHGAP4 were found to be high in SW620, SW480, and HCT116 cell lines, while they were being low in HT29, LoVo, and NCM460 cell lines. Depletion of ARHGAP4 resulted in inhibited proliferation and growth in SW620 cells and inhibited subcutaneous tumorigenesis in nude mice, whereas overexpression of ARHGAP4 promoted proliferation and growth in HT29 cells and promoted subcutaneous tumorigenesis in nude mice. A total of 318 upregulated genes and 637 downregulated genes were identified in SW620 cells upon ARHGAP4 knockdown. The downregulated genes were primarily associated with cell cycle pathways, while the upregulated genes were enriched in differentiation-related pathways. Notable upregulated genes involved in cell differentiation included KRT10, KRT13, KRT16, IVL, and CD24, while significant downregulation was observed in genes related to the cell cycle such as CCNA2, CDKN2C, CDKN3, CENPA, and CENPF. ARHGAP4 expression is markedly elevated in the M1 stage of CRC compared to the M0 stage, suggesting ARHGAP4 linked to the metastatic in CRC. ARHGAP4 regulates the proliferation and growth of colon cancer cells by up- and downregulated cell cycle and differentiation-related molecules, which may be related to the metastasis of CRC.